2012
DOI: 10.2478/v10177-012-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Parameters Assessed from Microwave and Optical Data

Abstract: The study has been carried out at Biebrza Wetlands situated in the N-E part of Poland, a NATURA 2000 and Ramsar Convention test site in 2003-2009. It is one of the largest in Europe natural rich biotope with the large amount of unique species of flora and important zone for nesting and wintering for fauna. Data from microwave and optical satellite images and soil-vegetation ground measurements were analyzed to develop methods for monitoring and mapping biophysical parameters. Satellite data applied for the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Table 7 (Figure 12 presents this relationship). The obtained relationship shows that with the increase of LAI there is an increase in the backscattering coefficient, which indicates the strong possibilities to monitor the increase of biomass using the long L wave of PALSAR data [10,36]. The relationship between LAI and biomass, which is strong for wetland vegetation habitats, has been elaborated by authors in previous studies and is described in papers [36][37][38].…”
Section: Prediction Of Leaf Area Indexmentioning
confidence: 79%
See 1 more Smart Citation
“…Table 7 (Figure 12 presents this relationship). The obtained relationship shows that with the increase of LAI there is an increase in the backscattering coefficient, which indicates the strong possibilities to monitor the increase of biomass using the long L wave of PALSAR data [10,36]. The relationship between LAI and biomass, which is strong for wetland vegetation habitats, has been elaborated by authors in previous studies and is described in papers [36][37][38].…”
Section: Prediction Of Leaf Area Indexmentioning
confidence: 79%
“…However, these satellite images have a spatial resolution of 1100 m, which was too low to classify the vegetation communities. We used high spatial resolution (but low temporal resolution) Landsat +ETM (Enhanced Thematic Mapper Plus), ALOS AVNIR-2 (Advanced Land Observing Satellite, Advanced Visible and Near Infrared Radiometer) and Terra ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer), as well as medium resolution ENVISAT MERIS (ENVIronmental SATellite MEdium Resolution Imaging Spectrometer) satellite images, for the classification of wetland's vegetation habitats in our previous study [11,36,37]. The results were satisfying as satellite images registered in the optical spectrum are widely used for land use/land cover mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Dorigo et al [64] presented the evaluation of CCI (Climate Change Initiative) soil moisture product using ground based observations. Soil moisture for the Biebrza Wetland has been investigated by authors in a previous study using microwave data acquired by ERS-1/2 SAR VV, ENVISAT ASAR IS2 HH, and ALOS PALSAR HH [25,43,44,65,66]. In the present study Sentinel-1 IW VV and VH data have been applied for the assessment of soil moisture (there was no S1 acquisition in HH polarisation).…”
Section: Soil Moisturementioning
confidence: 99%
“…This was done for the wetland habitats distinguished from the classification of MERIS image. LAI prediction, applying ALOS PALSAR HV data, was presented by Dabrowska-Zielinska et al in [43,65,66]. The obtained results showed that with the increase of LAI there was an increase in the backscattering coefficient, which indicates the low signal attenuation by vegetation in L-band, contrary to results obtained in C-and X-band.…”
Section: Influence Of Lai and Soil Moisture On σ° Calculated From Senmentioning
confidence: 99%
“…Thus, mapping various biophysical parameters of wetlands has attracted interest in a variety of ecological, environmental studies in recent years, including their distribution, leaf area index, biomass, etc. [3][4][5]. Above ground biomass (AGB) has been frequently analyzed among these parameters, which is defined as the total biomass of foliage and woody components of a vegetation canopy above the ground level [6].…”
Section: Introductionmentioning
confidence: 99%